PERAN LATIHAN PERCEPATAN DAN PEMULIHAN DALAM MENINGKATKAN KETAHANAN DAN DAYA TAHAN ATLET TENIS MEJA - Damayanti, Elsa (Perkumpulan Dosen Muda Bengkulu, 2024)
In the current era of increasingly competitive sports, table tennis athletes must have optimal physical condition to be able to compete effectively. Endurance and endurance are key factors that allow athletes to remain consistent and strong during long-lasting competitions. Optimal physique can increase athletes' self-confidence and motivation, because they feelÂ more physically and mentally prepared to face challenges on the field. This research aims to identify the role of acceleration and recovery training in increasing endurance and endurance in table tennis athletes. The research method used is a qualitative descriptive method through literature study sourced from journals, scientific articles, books and other relevant sources. The results of this study indicate that there are various forms of acceleration and recovery training to increase the endurance and endurance of table tennis athletes. Acceleration and recovery training plays an important role in increasing the endurance and endurance of table tennis athletes. Through structured and consistent training, athletes can improve their physical and mental abilities to survive long, stressful matches.